PROSPECTS FOR THE DEVELOPMENT OF PILGRIMAGE AND RELIGIOUS TOURISM - Vakhidov Sukhrobjon (Scholar Express Journal, 2025)
This article presents important insights into the economic, spiritual, and social significance of sacred pilgrimage sites, as well as the mechanisms for enhancing tourism potential and effective ways to utilize them. Additionally, by studying places of worship and sacred sites of various religions, we can observe pilgrimage regulations, achievements, and shortcomings. Therefore, pilgrimage tourism is one of the most active forms of travel, and all available opportunities should be utilized for its development.
Keywords: Pilgrimage tourism; religious tourism; tourist migration